Development of non-destructive technique for metallographic studies - Yu, Cunyang. (2011)
Surface replication is a well established non-destructive evaluation (NDE) technique for the determination of microstructural deterioration and damage of materials subjected to various environmental conditions. In comparison with other conventional NDE techniques, surface replication has its unique features and advantages. It can detect small microstructural changes, as well as micro fissuring or cracks. The replica obtained provides a permanent record of the specimen and therefore enables close monitoring of microstructural changes with service time and assessment of a component's remnant life. With the introduction of the surface replication technique, this paper demonstrates the use of methylcellulose and polydimethylsiloxane (PDMS) as replicating materials on carbon steel, and discusses the advantages and short comings of each material. The discussion is substantiated by data from laboratory studies.